2012
DOI: 10.3171/2011.9.jns111059
|View full text |Cite
|
Sign up to set email alerts
|

Impact test comparisons of 20th and 21st century American football helmets

Abstract: The authors do not advocate reverting to leather headgear, but they do strongly recommend, especially for young players, instituting helmet safety designs and testing standards, which encourage the minimization of linear and angular impact doses and injury risks in near- and subconcussive head impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…More recently, others compared the response of a NOCSAE headform on a Hybrid III neckform when struck by a swinging, helmeted NOCSAE headform (Bartsch et al, 2012). They examined five impact locations using three different impact speeds and found that leather helmets performed as well or better than modern helmets in terms of reducing linear, and angular accelerations.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, others compared the response of a NOCSAE headform on a Hybrid III neckform when struck by a swinging, helmeted NOCSAE headform (Bartsch et al, 2012). They examined five impact locations using three different impact speeds and found that leather helmets performed as well or better than modern helmets in terms of reducing linear, and angular accelerations.…”
Section: Introductionmentioning
confidence: 97%
“…Helmet designs have also greatly improved as the risk of concussions is better understood (Hodgson, 1975;Bartsch et al, 2012;Viano et al, 2006). Laboratory measurements of head acceleration, while wearing a helmet, have been conducting using linear impact and angular impact methods.…”
Section: Comparison Of Acceleration Sensors For American Football Helmentioning
confidence: 96%
“…An initial comparison of leather helmets to varsity helmets, evaluating several parameters including angular acceleration, linear acceleration, neck force and neck moment, showed that the risk of head injury may be comparable even with the use of leather helmets [95]. A more thorough study comparing varsity helmets with leather helmets showed consistent superiority of varsity helmets in head protection [96] and prior finding by Bartsch et al was attributed to lower impact energy (impact velocity of 5.0 m/s) and impactor set up that added compliance to the system and masking their differences.…”
Section: Footballmentioning
confidence: 99%